THE CONCEPT OF THE HUMAN BODY IN THE HOLY AL QUR'AN AND ITS IMPLICATIONS AGAINST ISLAMIC EDUCATION - Euis Latipah; Andewi Suhartini; Nurwadjah Ahmad EQ (UNIVERSITAS PAKUAN, 2021)
Humans are creatures that Allah SWT created perfectly from the essence of the soil, then become nuthfah, then become mudzgoh and become bones wrapped in meat to form the human body. With this perfection, the human task is always to be grateful and to maintain this potential. Al-Qur'an invites people to think about the origin of humans about their creation. Because in the human body there is a sign of great power that shows the majesty of Allah SWT. The research method in this journal uses a type of qualitative research with a literature approach. The data was collected by searching related reference book sources. After the data is obtained then the data is analyzed and some additions from the researcher. In this study, researchers found several results and conclusions in the discussion of the human body in the Koran, that the verses of Allah on the human body are very clearly explained in the Koran, which at that time had no biological research. Second, the concept of the human body has implications for Islamic education.